Kedudukan Pengadilan Pajak dan Perbandingannya dengan Sengketa Tata Usaha Negara di Indonesia - Jadidyah, Havida; Priyono, Agus (Universitas Muhammadiyah Ponorogo, 2025)
The Tax Court is a special judicial institution authorized to handle tax disputes in Indonesia. Its position is under the Supreme Court in terms of judicial technical guidance, but administratively, organizationally, and financially it is under the Ministry of Finance. This study aims to examine the position of the Tax Court in the Indonesian judicial system and to compare the mechanisms for resolving tax disputes with State Administrative (TUN) disputes. This study uses a normative legal method with a statutory regulatory approach and a conceptual approach. The results of the study indicate that the Tax Court is part of the state administrative court environment, but has specific procedures and authorities. The striking difference between tax disputes and TUN disputes lies in the resolution mechanism. Tax disputes are quasi-judicial in nature and require an objection procedure to the Director General of Taxes before they can be submitted to the Tax Court. In contrast, TUN disputes can be submitted directly to the State Administrative Court without going through the administrative objection stage. In addition, the decision of the Tax Court is final and binding, while the PTUN decision can still be pursued for further legal action. This difference reflects the characteristics of each dispute, and emphasizes the strategic position of the Tax Court in providing justice and legal certainty for taxpayers. This study is expected to contribute to strengthening the understanding of academics, legal practitioners, and the public regarding effective and targeted tax dispute resolution mechanisms.